1994
DOI: 10.1159/000247091
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Skin Metastasis from Follicular Thyroid Carcinoma

Abstract: We present a case of skin metastasis from follicular thyroid carcinoma which developed on the scalp of a 72-year-old man. The lesion was noticed 1 month after a surgical excision of the primary thyroid carcinoma and gradually enlarged during the past 11 months. A biopsy from the nodule showed mostly well-differentiated thyriod follicular structures with colloid material. Tumor cells showed mild variation of nuclear size and shape in almost all areas. We performed immunohistochemistry using antithyroglobulin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…[15] Face, neck, chest, arm and pelvis are the other cutaneous sites of metastasis affected with scalp. [16][17][18][19] Eighteen cases of FTC metastasis to scalp were reported in the literature [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Two cases reported by Lissak et al [20] were follicular microcarcinoma revealed by solitary scalp lesions.…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…[15] Face, neck, chest, arm and pelvis are the other cutaneous sites of metastasis affected with scalp. [16][17][18][19] Eighteen cases of FTC metastasis to scalp were reported in the literature [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Two cases reported by Lissak et al [20] were follicular microcarcinoma revealed by solitary scalp lesions.…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…When they do occur, they are found in the head and neck area, particularly the scalp 9,10 ; a number of cases of follicular thyroid carcinoma with scalp metastases have been reported. 5,9,11 In a series by Mondal et al, 5 follicular carcinoma of the thyroid accounted for 30% of metastatic deposits in the scalp. Scalp metastases from thyroid carcinoma result from malignant cells migrating along the external carotid artery.…”
Section: Discussionmentioning
confidence: 97%
“…secondary malignancy may have arose from a hip bone metastasis extending outwards into the surrounding soft tissue, but the appearance of the CT scan with the bulk of the tumor centered within the medial thigh compartment and pelvis suggests that the metastasis may have occurred within the soft tissue or skin, invading inwards. There have been reports of metastatic follicular thyroid carcinoma to the skin (5,6). Metastases to these unusual sites were often associated with widespread internal metastatic disease and poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%